Analisis Penerapan Akuntansi Keuangan Berdasarkan PSAK NO 1 pada Badan Usaha Milik Desa (BUMDes) di Desa Pandesari Kecamatan Pujon Kabupaten Malang - Maulidia Nur Zahrotun Na’imah; Nur Diana; Dewi Diah Fakhriyyah (e_Jurnal Ilmiah Riset Akuntansi, 2023)
This study aims to analyze the application of financial accounting at the BUMDes Pandemasmulya in Pandesari Village, Pujon District, Malang Regency. The researcher uses a qualitative descriptive type of research. The unit analysis used in this study includes President Director of BUMDes and Treasurer of BUMDes. The types and resources of data are primary data and secondary data obtained directly from BUMDes Pandemasmulya office. Data collection techniques using documentation and interview. Bumdes Pandemasmulya does not present balance sheets, reports on changes in equity and notes on financial statements. This BUMDes only presents daily cash reports, profit and loss reports and cash flow reports. The result of study that the financial statements and income statements of BUMDes Pandemasmulya were not in accordance with PSAK No. 1. Keywords: BUMDes, Application of Financial Accounting, PSAK No.1